Damage Control Surgery: A Strategic Resource! - Sánchez, Morelos Adolfo García; Hernández, José Luis García; Cabello, José de Jesús Urbina; Barrón, Gema Méndez; Castillo, Luis Fernando Flores; Salvador, Judá Raquel Hernández; Suárez, Ivonne Alondra León; Daniel, Mayra Yadira Pérez; Oca Ambriz, Iñaki Rubén Montes (British Journal of Healthcare and Medical Research, 2025)
Introduction: damage control surgery is a surgical strategy, applicable to traumatic and non-traumatic patients, in a context of severe physiological instability, addressing a complex surgical situation in stages. Objective: experience of the strategy of damage control surgery in trauma surgery, complicated elective surgery or a non-traumatic surgical emergency. Method: retrospective, longitudinal, observational and descriptive study. Reviewing the records of patients treated surgically applying damage control surgery, for 5 years. Results: 21 of 221 patients were documented applying the strategy, 9.95%, 19 were men (90.47%), 2 women (9.53%) with an average age of 25 years, range 17 to 64 years. Discussion: hemorrhagic shock is the most common immediate cause of death in trauma and requires immediate and coordinated action to reverse it. When there are few resources or limited infrastructure, trauma surgeons take the options of resuscitative thoracotomy and/or abdominal packing, at lower costs. Observations: the surgical technique of damage control surgery and the reasons that support it for the first time are detailed; coining innovative terms such as: "damage control surgery cycle", "planned hemostatic compression", "infection containment" Conclusions: damage control surgery is an effective, economic, and ethical strategic resource, which, if well carried out and allowed by the case, saves human lives and with an early closure cycle reduces morbidity, without sequelae and mitigates mortality.